PENDIDIKAN KEWARGANEGARAAN DAN KEBANGKITAN BANGSA - Charunie, Baroroh (PKn Progresif, 2008)
Indonesian nation as a nation is a great nation that does not forget its history, 100 years of the nation digaungkan by Budi Oetomo still marked by many shortages, corruption, lack of education and welfare. All this requires the resurrection life back nationalism, patriotism and civic education to the resurrection created human Indonesians sagacious a new, independent, prosperous and responsible and have the morals that mlia. U.S. citizens who uphold the values of noble culture, to anticipate the development of intelligent life that will come. This is all the duties and obligations as civic education and educational institutions that taught civilization means the task of teachers across the country in the U.S. to realize the sense of learning in order to achieve the favor of the ideal nation with a sense of nationalism has the strongest that good.